2018
DOI: 10.3390/su10062004
|View full text |Cite
|
Sign up to set email alerts
|

Improving Sustainability through Corrosion Resistance of Reinforced Concrete by Using a Manufactured Blended Cement and Fly Ash

Abstract: Abstract:The objective of this paper is to report the improvement of sustainability through the increase of reinforced concrete corrosion resistance by using a blended cement and fly ash. Different reinforced concrete mixtures were prepared with partial substitution of a manufactured blended cement with fly ash from a thermal power plant in Andorra (Teruel, Spain). These mixtures were manufactured using three different water/cement ratios (0.46, 0.59, and 0.70) and three substitution percentages of cement by f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Due to its relatively low cost and high compressive resistance capability, reinforced concrete is frequently used as a construction material worldwide. However, several aggressive agents found in the environment degrade steel reinforcements, cement, and concrete [1]. Corrosion of steel embedded in concrete was extensively studied since the 1950s, and, in the last 30 years, research concentrated on minimizing the steel corrosion rate.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its relatively low cost and high compressive resistance capability, reinforced concrete is frequently used as a construction material worldwide. However, several aggressive agents found in the environment degrade steel reinforcements, cement, and concrete [1]. Corrosion of steel embedded in concrete was extensively studied since the 1950s, and, in the last 30 years, research concentrated on minimizing the steel corrosion rate.…”
Section: Introductionmentioning
confidence: 99%
“…To accurately assess the ascending section and descending sections of the stress-strain curve of acid-corroded concrete, the piecewise expression was used to fit the measured stress-strain curve of corroded concrete, which truly reflected the mechanical properties of concrete corroded by hydrochloric acid. In this section, the measured compression stressstrain curve of acid-corroded concrete under cyclic load was treated dimensionless by using the dimensionless method, and then the fitting formula of the stress-strain envelope curve was determined by the stress-strain relationship curve constitutive model proposed by Ding et al [47,48], as shown in Equations ( 10)- (12).…”
Section: Model Establishmentmentioning
confidence: 99%
“…In particular, the concrete members in the sulfuric acid or hydrochloric acid corrosion environment [1][2][3][4][5][6]. Several investigations indicated that acid corrosion had become one of the major threats affecting the mechanical properties of RC structures [7][8][9][10][11][12], resulting in the reduction of bearing capacity and ductility. Meanwhile, the double coupling actions of acid corrosion and load not only affected the durability of concrete structures but also made the calculation method used in the existing design no longer applicable to the concrete severely corroded by acid, endangering the safety of structures.…”
Section: Introductionmentioning
confidence: 99%
“…The use of any kind of FA to produce cement composites is reasonable only in the case of obtaining the assumed technological properties of such materials, and first of all, durability. The problem of durability of cement composites was the subject of numerous publications [28][29][30][31]. The reason for that is the high pollution level of the atmosphere and water, which increases the aggressiveness of the environment and the speed of corrosion.…”
Section: Introductionmentioning
confidence: 99%